Species Diversity of Mangroves in Central Zambales, Philippines - SERRANO, Shirly C.; TANGTHAM, Nipon; BUALERT, Surat; JANYASUTHIWONG, Suthee (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
The Philippines being an archipelagic country has one of the most diverse mangrove ecosystems.  Species composition and diversity assessment are vital for sustainable management and conservation activities of mangrove resources. The diversity of mangroves was assessed to determine the status of the mangrove ecosystem in the central part of Zambales, Philippines. Data were gathered using a random quadrat sampling method in the twelve pre-selected stations. Each quadrat measures 1  meters and the quantitative description of each plant species was determined. There were a total of 15 mangrove species surveyed in the area, under seven families, which family Rhizophoraceae was the most represented, with six species, and families Euphorbiaceae, Meliaceae, and Myrsinaceae were only represented with one species each. Shannon’s Diversity Index showed that the mangrove ecosystems in Botolan had “very low” diversity (SDI=1.71) and Iba had “low” diversity (SDI=2.11). Anthropogenic sources such as agri-aqua and encroachment served as the major driving forces in the diversity of mangroves. Other threats include solid waste disposal, quarrying, oil spill, organic fertilizer run-off, and soil erosion among others. These may threaten species that could eventually cause greater biodiversity and economic loss. Hence, protection, conservation, and sustainable management be given priority.